Education in Cultural Heritage: A Case Study of Redesigning Atayal Weaving Loom - Rungtai Lin; I-Ying Chiang; Yuma Taru; Yajuan Gao; John G. Kreifeldt; Yikang Sun; Jun Wu (MDPI AG, 2022)
Employing cultural ergonomics concepts to product innovation for cultural education and sustainable development is the target of this study. Atayal culture is famous for its weaving craft and art. The Atayal tribe of Taiwanese aborigines weave on the Atayal loom. Traditional culture is disappearing rapidly due to colonial history and modernization. The Atayal people consider the weaving loom a cultural object when used as a weaving device. This study attempts to transform the ancient Atayal loom into a teaching device and extend Atayal weaving from execution in daily living to cultural experience and cultural heritage development. This study first explores and identifies the meaning of cultural objects and extracts their cultural features. Then, employing cultural ergonomics, a weaving box is redesigned from an ancient part of the loom into a modern weaving box. Finally, the new weaving device is evaluated and discussed. This case study examines a paradigm of how designers interact with cultural heritage and transform cultural objects into new instructional aids. Through cultural product design, it provides an intertwined experience in theoretical and practical approaches to accomplishing the development of cultural sustainability.